Poselitev kot prostorski sistem in predmet obravnave v prostorskem načrtovanju - osnovni pojmi - Hazler-Papič, Milena (Urbani izziv, 2004)
As the spatial planning on the state and municipality level for the period between 1984 and 2000 (2004) is no longer in value, the focus is set on the changes in the field on settlement planning. The new Law on spatial planning introduced these changes. The new technology, in comparison with the previous one, does not bring any crucial improvement. Some of the newly introduced notions caused an unnecessary confusion in the already set semantic field. A definition of the settlement system as a special component has been ignored, which shows that it was incompletely and insufficiently analysed. In order to obtain appropriate terminology in the field of settlement spatial system, the latter has to be recognised as a system that, at the same time, is an independent ministerial department. The settlement development planning as well as its introduction into the spatial planning process is only one of the possible perspectives of the settlement analyses. This article presents basic analyses of the spatial planning system as well as thereby connected terminology.
Keywords: naselja; poselitev; prostorski plani; prostorsko planiranje; spatial planning